A Novel DFNA36 Mutation in TMC1 Orthologous to the Beethoven (Bth) Mouse Associated with Autosomal Dominant Hearing Loss in a Chinese Family - Zhao, Yali (Public Library of Science, 2014)
Mutations in the transmembrane channel-like gene 1 (TMC1) can cause both DFNA36 and DFNB7/11 hearing loss. More than thirty DFNB7/11 mutations have been reported, but only three DFNA36 mutations were reported previously. In this study, we found a large Chinese family with 222 family members showing post-lingual, progressive sensorineural hearing loss which were consistent with DFNA36 hearing loss. Auditory brainstem response (ABR) test of the youngest patient showed a special result with nearly normal threshold but prolonged latency, decreased amplitude, and the abnormal waveform morphology. Exome sequencing of the proband found four candidate variants in known hearing loss genes. Sanger sequencing in all family members found a novel variant c.1253T>A (p.M418K) in TMC1 at DFNA36 that co-segregated with the phenotype. This mutation in TMC1 is orthologous to the mutation found in the hearing loss mouse model named Bth ten years ago. In another 51 Chinese autosomal dominant hearing loss families, we screened the segments containing the dominant mutations of TMC1 and no functional variants were found. TMC1 is expressed in the hair cells in inner ear. Given the already known roles of TMC1 in the mechanotransduction in the cochlea and its expression in inner ear, our results may provide an interesting perspective into its function in inner ear.